(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Production of Medium Density Fibreboards (MDF) is one of the growing woodworking industries. It has been found that a quarter of the produced MDFs have a life cycle of up to five years, and by ten years, this amount has increased to fifty percent. There is no established industrial practice for recycling that type of waste. That, together with the fact that some countries have banned the dumping of these panels in landfills, poses significant challenges. There are currently two main research directions on MDF recycling, namely with and without pre-treatment. In both cases, with an increase in the content of recycled fibres, a deterioration in the properties of the panels is observed. Still, the share of cut fibres and formaldehyde emissions from the boards are reduced during the preliminary treatment, mainly by hydrolysis. In the present manuscript, a review and analysis of MDF recycling methods are performed. On that base, conclusions and recommendations are derived.